Waste Management with Lean Methods in the Coffee Industry - Rebeka*, Aprilia Wita; Hartono, Markus (Riwayat: Educational Journal of History and Humanities, 2023)
According to data from Euromonitor, the estimated sales volume of ready-to-drink coffee in Indonesia in 2022 stood at approximately 225 million liters. This figure represents a 3.2% growth compared to the preceding year. This upswing serves as a catalyst for the coffee industry to enhance its productivity and respond swiftly to the competitive landscape. Augmented production levels are anticipated to result in a rise in waste generation. This study explores waste management and lean concepts through an empirical research article, emphasizing the necessity of implementing lean principles to streamline waste.In the present-day fiercely competitive and demanding market, all manufacturing sectors must continuously strive to endure. Companies, in their pursuit of success, confront stiff competition amid resource constraints. To attain their objectives, companies employ various strategies. Stakeholders endeavor to integrate cutting-edge and innovative methodologies into their production systems with the aim of achieving effectiveness and efficiency. A critical stride towards achieving efficient workflow is comprehending the waste that arises within the production process and striving to diminish its presence. The lean manufacturing approach emerges as a potent philosophy, offering an array of tools and strategies to guide companies in enhancing their quality. This approach proves beneficial across multiple sectors, encompassing the identification and elimination of waste, improvement in product and service quality, cost reduction in production, decreased reliance on human labor, and reduced production cycle time. In this study, the coffee industry serves as the focal point, applying the lean manufacturing approach to pinpoint waste within the production process and bolster value-added activities across the entire process. The ultimate objective is to heighten process efficiency and achieve a lean operation.